(untitled) (Communications in Mathematical Research, 2021)
In this paper, we first introduce the concept "harmonically convex functions" in the second sense and establish several Hermite-Hadamard type inequalities for harmonically convex functions in the second sense. Finally, some applications to special mean are shown.